Systematic review and meta-analysis of the efficacy of olprinone and MEFV gene in treating heart failure: Effect of olprinone and MEFV gene in heart failure - Fu, Yuhong; Wang, Xiaoyue; Pan, Yonggui; Zhang, Haibo (Cellular and Molecular Biology, 2023)
Cardiovascular failure is the main cause of death in industrialized societies. The results of recent studies have shown that some mutations in the MEFV gene are common in heart failure patients. For this reason, the study of mutations and genetic factors has been of great help in the treatment of this disease, but despite this, due to the heterogeneity of clinical symptoms, multiple pathophysiological processes, and environmental genetic factors, the complete understanding of the genetic causes of this disease is very complicated. As the new generation of phosphodiesterase (PDE) III inhibitor, olprinone, the inhibition of human heart PDE III by olprinone is highly selective. It is suitable for the treatment of acute heart failure (HF) and acute cardiac insufficiency after cardiac surgery. In this study Olprinone, milrinone, PDE inhibitors, cardiac failure, and HF were selected as the search terms to retrieve articles published between January 1999 and March 2022. RevMan5.3 and Stata were employed to analyze and evaluate the risk bias of the included articles. Besides, the Q test and heterogeneity were utilized to evaluate the heterogeneity between articles. The results of this research showed No heterogeneity was found between each research group. The sensitivity (Sen) and specificity (Spe) of the two methods were compared. Olprinone showed more significant therapeutic effects than other PDE inhibitors. Besides, the therapeutic effect on the patients with HF in the two groups was obvious. The incidence of postoperative adverse reactions among the patients without relieving HF was low. The influences on urine flow of the two group's demonstrated heterogeneity, and its effect revealed no statistical meaning. The meta-analysis confirmed that the Spe and Sen of olprinone treatment were higher than those of other PDE inhibitors. In terms of hemodynamics, there was little difference between various treatment methods.